SYMBOL SENSE ABILITY OF JUNIOR HIGH SCHOOL PROFESSIONAL MATHEMATICS TEACHERS - muhamad badrul mutammam; Dwi Juniati; Siti Khabibah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Symbol sense is the intuitive feeling of calling out symbols in the process of solving problems. Professional teachers are teachers who have graduated from the Teacher Education Program (PPG). This qualitative descriptive study aims to describe the symbol sense ability of junior high school professional mathematics teachers. Three subjects are mathematics teachers who have passed PPG. Data were collected through six symbol sense tasks adapted from Jupri and Suspiyati and interviews. Assignments and interviews were analyzed using the triangulation method proposed by Miles, Huberman, and Saldana. The findings reveal that professional teachers tend to have good symbol sense abilities. In the second symbol sense characteristic, two out of three teachers display a poor symbol sense performance by manipulating the equation directly rather than reading the assignment in depth-first to get a better understanding so that they can complete the task correctly and efficiently. The teacher should improve his symbol sense ability.